Self-Management in Children with Sickle Cell Anaemia in Enugu, Nigeria - Eneh, C. I.; Ogbuka, F. N.; Nzeduba, C. D. (British Journal of Healthcare and Medical Research, 2022)
Sickle cell anaemi (SCA) is a chronic, genetic disorder of haemoglobin structure resulting from inheritance of two abnormal ‘S’ globin genes. It is a disease characterized by episodic exacerbation (crises) of chronic low-grade haemolysis and vaso-occlusion and complicated by multiple infarcts of organ-systems which impair quality of life. Most crises occur and are managed at home. The frequency of pain crises and resulting hospitalizations may therefore increase without appropriate self-care at home. Self-care include therapeutic activities (self-action) that prevent complications, aid coping, improve psychosocial and health status as well as the individual’s perceived ability (self-ability) to perform these activities. An effective self-care plan requires an initial recommendation by a health care practitioner and is pivotal in the successful management of SCA in resource limited setting where secondary prevention strategies prevail. However, self‐care recommendations in SCA are limited, inconsistent and poorly complied to. The study aims to examine the self-care patterns and practices of Paediatric SCA patients in a tertiary hospital.